The Effect of Sansevieria Plant on Particulate Matter 2.5 Levels in Classroom (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
The Poor physical environment is the main cause of acute respiratory infections that result in death in school children aged 5 to 14 years due to exposure to PM2.5 at school. The improvement of the school’s physical environment from high PM2.5 pollution is to involve the school community in planting Sansevieria Trifasciata as a solution to reducing PM2.5 pollution. This study aims to analyze the significance of differences in the physical environmental conditions of the Ciranjang 1 State Elementary School, Cianjur Regency, on the level of respiratory susceptibility of students seen from PM2.5 levels before and after the placement of Sansevieria Trifasciata. The study used 2 test classes and 1 control class. The study duration was 24 hours with two measurements, namely at the pretest and posttest. Data analysis used the Ancova one-way test followed by the Post-Hock test. The placement of 8 pots of Sansevieria Trifasciata was able to absorb PM2.5 compared to 6 pots of Sansevieria trifasciata. There is an effective and significant absorption of PM2.5 pollutants by placing 8 pots of Sansevieria trifasciata plants in a 49m2 classroom, which is 29µgr/m3 on the respiratory vulnerability level of Ciranjang 1 State Elementary School students, Cianjur Regency.